An Outbreak of Vancomycin-Resistant Enterococci in a City Hospital Intensive Care Unit: Molecular Characterization of Resistance - Senol, Feray Ferda; Tanriverdi, Elif Seren; Aytac, Ozlem; Toraman, Zulal Asci; Otlu, Baris (Mdpi, 2023)
Background and Objectives: Vancomisin-resistant Enterococci (VRE), is a resistant microorganism that colonizes and causes infections in hospitalized patients. The aim of this study was to show the spread of vancomycin-resistant Enterococcus faecium (VREfm) step-by-step in all intensive care units, which started with the growth of VREfm on 2 December 2021 in the blood culture of a patient hospitalized in the anesthesia intensive care unit of our hospital and was found to have reached epidemic size in the surveys. Materials and Methods: Rectal swab samples were taken from all patients hospitalized in intensive care units, VRE colonization was determined, the VanA and VanB resistance genes associated with the vancomycin resistance of VREfm isolates were determined by PCR method, and clonal association analysis was performed by Arbitrarily Primed-PCR (AP-PCR) and PFGE (pulsed-field gel electrophoresis). Results: In our study, VRE were detected in 61 of 2601 rectal swab samples. In total, fifty-four (85.52%) of the VRE isolates were Enterococcus faecium, three (4.91%) was Enterococcus faecalis, three (4.91%) was Enterococcus gallinorum, and one (1.63%) was Enterococcus casseliflavus. It was determined that all of the 54 VREfm isolates, which were the most detected among all VRE isolates, carried the vanA gene. In the clonal association analysis of the isolates by AP-PCR and PFGE methods, it was found that they had 12 different genotypes, 48 of them were included in any cluster, the clustering rate was 88.8%, and the largest cluster was the genotype 1 cluster, with 36 isolates. Of the 54 patients with VREfm isolated recently, 18.51 percent of the clinical samples were isolated before the survey, and 9.25% were isolated after the survey. It was determined that 100% of VREfm isolates were resistant to ampicillin, levofloxacin, ciprofloxacin, high-level gentamicin, trimethoprimsulfamethoxazole, and teicoplanin, 7.4% to tigecycline, and 1.85% to linezolid. Conclusions: In our study, in the clonal association analysis performed by isolating VREfm in rectal swab samples, it was found that 88.8% of the samples were indistinguishably similar, and that the increase in the number of VREfm infections after the index case in our hospital was associated with the epidemic. VREfm infections cause long-term hospitalization, costs and also deaths, which shows the seriousness of the event, and the importance of the combination of epidemiological and molecular analysis in epidemic research.
Keywords: vancomycin-resistant Enterococcus faecium; hospital epidemic; whole-genome analysis; infection prevention and control